Mulberry Juice-Derived Carbon Quantum Dots as a Cu2+ Ion Sensor: Investigating the Influence of Fruit Ripeness on the Optical Properties - Chiayee Salih Ajaj; Diyar Sadiq (Nanomaterials and Nanotechnology)
This study synthesized carbon quantum dots (CQDs) with green photoluminescence through a hydrothermal method that utilized mulberry juice as the carbon source. The influence of fruit ripeness on the physical and chemical properties, focusing on the fluorescence spectra, has been explored. Fourier-transform infrared spectroscopy (FT-IR) and energy dispersive X-ray analysis (EDX) showed that there were oxygen-containing groups, and X-ray diffraction (XRD) showed that the carbon quantum dots (CQDs) were graphitic. The results revealed that the CQDs had an average size of around 7.4 nm and 9.7 nm for unripe and ripe mulberry juice, respectively. These CQDs emitted green light at 500 nm and 510 nm in unripe and ripe mulberry juice, respectively, when excited at a wavelength of 400 nm. The prepared CQDs exhibited excitation-dependent photoluminescence (PL) emission behavior, demonstrating their dependence on the excitation light. The impact of fruit ripeness on optical properties was explored by examining fluorescent spectra from different fruits (including tomato and blackberry), demonstrating comparable behaviors observed in mulberry fruit. In addition, the prepared CQDs were utilized as a fluorescent sensor with high specificity to detect Cu2+ ions. The detection limit (DL) for this sensor was determined to be 0.2687 µM, and the limit of qualification (LOQ) is 0.814 µM. The linear range for detection lies between 0.1 and 1 µM. The selectivity of the CQDs towards Cu2+ ions was confirmed by recording the PL response for Cu2+ ions compared to the weak response of other metal ions. According to these results, the CQDs can be applied in various cellular imaging and biology applications, bio-sensing, optoelectronics, and sensors.